Desert and ruins — landscapes of anger and traces of unbelief (landscape and Scripture) - S. S. Vaneyan (Российский журнал истории Церкви)
The article treats of the experience of using two fundamental motives in architectural semantics — “desert” and “ruin” in order to resolve the hermeneutic paradox, which is peculiar to sacred architecture, considered in the context of Abrahamic tradition: canonical texts related to architecture either prescribe, or describe construction experience. Yet, purely construction motives can be supplemented not only by motives of creation, but also motives of destruction. Thus, the necessary critical (crisis) position of interpretation will be provided, revealing the pre- and post-architectonic dimensions of theophanic experience. The rhetorical topic of “desert” and “ruin” has two dimensions: one deals with phenomena of space and object, and the other with literary metaphors. Both are presented in the article in a threefold sequence: literature is replaced by the theory of memory, which in turn passes the baton to philosophy, primarily the philosophy of space, but also of time, with a return to history, either asserted or cancelled.